2011
DOI: 10.2165/11591970-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren as Add-On Therapy in the Treatment of Hypertensive Diabetic Patients Inadequately Controlled with Valsartan/HCT Combination

Abstract: The reductions in BP with aliskiren added to valsartan/HCT in this study were numerically greater compared with placebo added to valsartan/HCT, although not statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…Six trials [ 14 - 19 ] involved in the analysis of antihypertension and the result suggested aliskiren in combination therapy with ACEs/ARBs was superior to ACEI or ARB monotherapy in SBP reduction (WMD, -4.20; 95% CI -5.44 to -2.97; I 2 , 29.7%) and DBP reduction (WMD, -2.09; 95% CI -2.90 to -1.27; I 2 , 0%) as described in Figure 3B .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six trials [ 14 - 19 ] involved in the analysis of antihypertension and the result suggested aliskiren in combination therapy with ACEs/ARBs was superior to ACEI or ARB monotherapy in SBP reduction (WMD, -4.20; 95% CI -5.44 to -2.97; I 2 , 29.7%) and DBP reduction (WMD, -2.09; 95% CI -2.90 to -1.27; I 2 , 0%) as described in Figure 3B .…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies [ 9 , 14 , 15 , 17 , 19 - 24 ] reported on the outcome of hyperkalaemia (Table 2 and Figure 3A ). Combination therapy was significantly associated with the risk of hyperkalaemia compared with an ACEI or an ARB monotherapy (RR 1.45; 95% CI 1.28 to 1.64; I 2 , 10.6 %).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ALI monotherapy was superior to RAM monotherapy for msSBP reduction and non-inferior for msDBP reduction [32]. The addition of ALI 300 mg in the VAL/HCTZ 160/25 mg regimen in diabetic individuals showed greater BP reductions, however this did not achieve statistical significance [60]. In a recent randomized control trial by Imbalzano et al, ALI addition to optimal antihypertensive therapy showed higher BP and microalbuminuria reductions than LOS or RAM addition in patients with uncontrolled BP and DM [79].…”
Section: Aliskiren and Blood Pressure Loweringmentioning
confidence: 99%
“…оценивали антигипертензивный эффект добавления Алискирена по сравнению с плацебо у 328 пациентов СД2 с неадек-ватным контролем АД на терапии Валсартаном 160 мг/сут и гидрохлоротиазидом (ГХТ) 25 мг/сут. Через 12 недель лечения снижение САД и ДАД было более выражено в группе больных, получавших Алискирен 300 мг в соче-тании с Валсартаном 160 мг и ГХТ 25 мг, по сравнению с группой плацебо, хотя различия не достигали уровня статистической значимости [12].…”
Section: результатыunclassified